Bleomycin-Induced Pneumonitis in the Treatment of Ovarian Sex Cord–Stromal Tumors: A Systematic Review and Meta-analysis. Issue 9 (1st November 2015) - Delanoy, Nicolas; Pécuchet, Nicolas; Fabre, Elizabeth; Combe, Pierre; Juvin, Karine; Pujade-Lauraine, Eric; Oudard, Stéphane
Abstract : Objective: Adult ovarian sex cord–stromal tumors (SCSTs) are a rare histological subtype of ovarian cancer associated with a favorable prognosis. Bleomycin-containing regimens are standards of care, although pneumonitis may cause potentially fatal dose-limiting toxicity. We aimed to evaluate the safety of bleomycin in SCST treatment. Methods: We performed a systematic literature review of all studies of bleomycin therapy for SCSTs that were referenced in MEDLINE (PubMed), EMBASE, and Cochrane Central Register of Controlled Trials and published from 1986 to 2014. Results: Eight studies totaling 221 patients were included. Rates of pneumonitis (7.7%; 95% confidence interval, 4.2–11.2) and mortality (1.8%; 95% confidence interval, 0.1–3.6) related to bleomycin were significant. However, these results were very similar to those reported for men who were treated with bleomycin for a male germ cell tumor, suggesting that women with ovarian SCSTs are not particularly vulnerable to bleomycin lung toxicity. The main risk factors of bleomycin-induced pneumonitis are high cumulative bleomycin dose (>400 U or mg), age older than 40 years, and impaired renal function. Whether granulocyte colony-stimulating factor is a risk factor remains controversial. Conclusions: Bleomycin-induced pneumonitis frequently occurs in patients with SCSTs and lacks effective treatment. Prevention lies in limiting cumulative bleomycin dose, monitoring pulmonary function during treatment, discontinuing bleomycin at the onset of pulmonary symptoms or if pulmonary function is impaired, and avoiding bleomycin in older patients.